2011
DOI: 10.1128/mcb.01000-10
|View full text |Cite
|
Sign up to set email alerts
|

Genomic mRNA Profiling Reveals Compensatory Mechanisms for the Requirement of the Essential Splicing Factor U2AF

Abstract: The large subunit of the U2 auxiliary factor (U2AF) recognizes the polypyrimidine tract (Py-tract) located adjacent to the 3 splice site to facilitate U2 snRNP recruitment. While U2AF is considered essential for pre-mRNA splicing, its requirement for splicing on a genome-wide level has not been analyzed. Using Solexa sequencing, we performed mRNA profiling for splicing in the Schizosaccharomyces pombe U2AF 59 (prp2.1) temperature-sensitive mutant. Surprisingly, our analysis revealed that introns show a range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 70 publications
8
22
0
Order By: Relevance
“…Although it is curious that knockdown of a core splicing factor like dU2AF 50 resulted in splicing changes at specific junctions and not a global down-regulation in splicing, this was consistent with previous studies that had shown similar effects with S. pombe U2AF temperature-sensitive mutants and RNAi depletion of Drosophila core spliceosome proteins (Park et al 2004;Sridharan et al 2011).…”
Section: Evolution Of Splicing Regulation Genes and Development 613supporting
confidence: 77%
See 1 more Smart Citation
“…Although it is curious that knockdown of a core splicing factor like dU2AF 50 resulted in splicing changes at specific junctions and not a global down-regulation in splicing, this was consistent with previous studies that had shown similar effects with S. pombe U2AF temperature-sensitive mutants and RNAi depletion of Drosophila core spliceosome proteins (Park et al 2004;Sridharan et al 2011).…”
Section: Evolution Of Splicing Regulation Genes and Development 613supporting
confidence: 77%
“…dU2AF 50 is a core splicing factor, and as such may not be expected to specifically regulate distinct transcripts. Nevertheless, our data are consistent with previous studies in which core spliceosomal factors did have such specificity (Park et al 2004;Sridharan et al 2011). Although the collection of splice junctions sensitive to dU2AF 50 and LS2 depletion overlapped to a small extent, the majority of them were unique to either protein (Fig.…”
supporting
confidence: 82%
“…Mutations in the nucleotides of the 5Јss consensus hexamer motif (G 1 -A and U2-A/G) in budding yeast cause lariat intermediate accumulation and second step arrest, whereas surprisingly, mutations in all nucleotides in the 5Јss hexamer sequence cause a block before any catalysis in fission yeast (51). Among the trans-acting factors, studies from our laboratory on SpSlu7, the ortholog of budding yeast second step factor, ScSlu7, also clearly show splicing arrest before catalysis (23). Fission yeast cells deleted for lariat debranching gene (dbr1⌬) have more severe growth defects than the corresponding budding yeast mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide splicing analyses of transcripts in a missense mutant of spslu7 ϩ revealed its requirement before the first step of the splicing reaction, its widespread but intron-specific functions, and its novel interaction with another precatalytic splicing factor (22). The dependence on fission yeast factors SpPrp2 (23) and SpPrp4 (24) correlates with specific intronic features in each case. Other studies with cwf10-⌬NTE mutant of the SpCwf10 splicing factor revealed that its role in splicing is general and not transcript-specific (25).…”
mentioning
confidence: 99%
“…There are introns which are spliced independently of the large subunit of the U2 auxiliary factor (U2AF 59 ). Noteworthy here, U2AF 59 is essential for growth [56][57][58]. Moreover, there is some evidence that the recruitment of U2AF 59 to auxiliary factor dependent introns might be mediated by the SR protein Srp2, which has been shown above to be an in vitro substrate of Prp4 kinase [26].…”
Section: Inhibition Of Prp4 Kinase Activity Affects Splicing Of Intromentioning
confidence: 99%